Evaluation of sleep disorders in cancer patients based on Pittsburgh Sleep Quality Index. (1st March 2015) - Akman, Tulay; Yavuzsen, Tugba; Sevgen, Zeynep; Ellidokuz, Hulya; Yilmaz, Ahmet Ugur
<x xml:space="preserve">Abstract</x> Insomnia, poor sleep quality and short sleep durations are the most common problems seen in cancer patients. More studies are needed about sleep disorders in cancer patients. In our study, we aimed to investigate the prevalence of sleep disorders and the impact of these problems on the quality of life in cancer patients. Pittsburgh Sleep Quality Index (PSQI) was given to a total of 314 patients. The psychometric evaluation of the Turkish version of PSQI in cancer patients revealed that 127 (40.4%) patients had global PSQI scores >5, indicating poor sleep quality. There was no statistically significant relationship between PSQI scores and sexuality, marital status, cancer stage and chemotherapy type (P > 0.05); while the patients with bone and visceral metastasis had much lower PSQI scores (P = 0.006). Patients with Eastern Cooperative Oncology Group performance scores of 3 or more had also significantly lower PSQI scores (P = 0.02). In conclusion, PSQI questionnaire may be used to evaluate the sleep disorders in cancer patients. Consistent use of multi‐item measures such as PSQI with established reliability and validity would improve our understanding of difficulties experienced by cancer patients with chronic insomnia.